Contractual relations : a contribution to the critique of the classical law of contract - Campbell, David, 1958- (Oxford : Oxford University Press, 2022)
Written by one of the leading contributors to the relational theory of contract, 'Contractual Relations' authoritatively explains the form of the existing law of contract by relating it to its economic, legal, and sociological foundations. This volume demonstrates that economic exchange and legal contract rest on a moral relationship by which each party legitimately pursues its self-interest through recognition of the self-interest of the author.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 1, 2022).
Keywords: Contracts; Contracts -- Moral and ethical aspects; Contracts -- Social aspects; Law; Laws of specific jurisdictions & specific areas of law